Public Opinion on the Company's Corporate Social Responsibility (CSR) - Muhammad Fasikhul Lisani; Ainur Rochmaniah (Indonesian Journal of Public Policy Review, 2022)
This research is a research with a quantitative descriptive approach whose data is in the form of qualitative data that is numbered, which will later be concluded to obtain the calculation results. The research location was carried out in the area of ​​Rw.05 and Rw.06 of Bringin Wetan Hamlet, Bringin Bendo Village, Taman District, Sidoarjo Regency. By using respondents as many as 88 respondents, by using the technique .Sampling using the technique of random .sampling. Collecting data through the distribution of questionnaires to respondents and interviews as complementary research materials. Data analysis using interval or percentage scale using Microsoft Excel 2010 and SPSS 20.0. The results of this research show that the overall opinion of the community about the activities of the Corporate Social Responsibility of PT. Charoen Pokphand has done well, this is shown from the results of the lowest opinion value in trust of 77.18% in the social field. Which is in the good category, while the highest opinion value in the social part of the attitude is 82.13% which is in the very good category. From these results it can be ascertained that the Corporate Social Responsibility activities of PT. Charoen Pokphand Indonesia – Sidoarjo East Java received positive opinions from the people around the company. However, there are still negative values ​​from residents which are caused by several factors, namely the lack of supervision from the company, the amount of assistance is not evenly distributed, information about the assistance is not conveyed properly to the community.